Disruptive forces on the electricity industry: A changing landscape for utilities - Tayal, Dev (Elsevier Inc., 2016)
© 2016 The energy sector has been navigating rapid technology innovation, slowing demand, and rising electricity prices. A steady shift towards renewable energy products is also exacerbating the disruption of utility business models. This article outlines the drivers of disruption for electricity utilities, and explores potential risks and opportunities should traditional business models evolve to embrace innovative technologies going forward.